Comparison of Culture Media for In Vitro Maturation of Oocytes of Indigenous Zebu Cows in Bangladesh - Joydev Kumar Singha; Mohammad Musharraf Uddin Bhuiyan; Mohammad Moshiur Rahman; Farida Yeasmin Bari (Journal of Animal Reproduction and Biotechnology, 2015)
The objectives of the present study were to select an effective basic medium including its hormone and protein supplementation for IVM of oocytes of indigenous zebu cows. The ovaries of cows were collected from slaughter house and the follicular fluid was aspirated from 2 to 8 mm diameter follicles. The COCs with more than 3 cumulus cell layers and homogenous cytoplasm were selected for maturation. The oocytes were matured in media for 24 hrs at 39℃ with 5% CO2 in humidified air. The maturation of oocytes was evaluated by examining the presence of first polar body under microscope. An efficient basic medium was determined after culturing COCs in either TCM 199 or SOF medium in Experiment 1. An efficient hormone supplementation was determined after culturing COCs in either FSH or gonadotrophin supplemented TCM 199 in Experiment 2. An efficient protein supplementation was determined after culturing COCs in either FBS or Oestrous cow serum (OCS) supplemented TCM 199 in Experiment 3. The oocyte recovery rate per ovary was 3.35. The overall rate of IVM was 74.6%. The maturation rate was 75.5±3.9 and 62.2±20.2% in TCM and SOF medium, respectively (P>0.05). The maturation rate of oocytes was significantly higher (76.6±13.2%) in FSH supplemented medium than gonadotrphin supplemented counterpart (69.7±10.8%) (P<0.05). The maturation rates of oocytes were 81.7±12.9 and 85.7±12.7% in medium supplemented with FBS and OCS, respectively (P>0.05). In conclusions, both TCM 199 and SOF supplemented with either FBS or OCS, and FSH may be used as medium for IVM of indigenous zebu oocytes in Bangladesh.